Correlation of ACE Gene Polymorphism and Hypertension in Stroke Ischemic Patients - Chandra, Vincent Alexander; Siregar, Yahwardiah; Arina, Cut Aria (Sumatera Medical Journal, 2020)
Stroke is the third highest cerebrovascular disease in the world with high mortality and disability rate that is mostly dominated by ischemic stroke. Genetic factor that had been reported to have an indirect effect in increasing the incidence of ischemic stroke is ACE gene polymorphism. ACE gene polymorphism is characterized by the insertion marked by letter (I) or deletion marked by letter (D) on intron 16, chromosome 17. ACE gene polymorphism has drawn a lot of attention from scientists and had been reported to have an indirect effect in increasing the ischemic stroke incidence through pathogenesis of hypertension and atherosclerosis. In this study, 78 subjects of ischemic stroke consist of 43 subjects with hypertension and 35 subjects with normotension. I allele of ACE gene polymorphism was more dominant than D allele in hypertensive ischemic stroke patients (72.1% > 27,9%) and this dominance was also seen in the incidence of hypertension vs normotension (55.4% > 44.6%). However, the correlation of ACE gene polymorphism with the incidence of hypertension was not statistically significant when compared based on its genotype (p=0.280) and allele (p=0.948).